Effects of exercise on pregnant women's quality of life: A systematic review. (November 2019) - Liu, Na; Gou, Wei-hui; Wang, Jie; Chen, Dan-dan; Sun, Wei-jia; Guo, Ping-ping; Zhang, Xue-hui; Zhang, Wei
Abstract: Objectives: Exercise is a promising approach to improve the health of pregnant women. However, data from studies investigating exercise and the quality of life of pregnant women are inconsistent and, to date, no systematic review on this topic has been published. The aim of this review was to comprehensively assess the effects of exercise on pregnant women's quality of life, and to determine whether exercise positively affects quality of life in this population. Study design: Literature was retrieved from electronic databases, namely PubMed, EMBASE, Web of Science and the Cochrane Library, from inception to 30 October 2018. Clinical trials published in English evaluating the effects of exercise on pregnant women's quality of life were included. The authors assessed the risk of bias in all eligible studies using the Effective Public Health Practice Project, and used a qualitative synthesis method to identify the effects of exercise on pregnant women's quality of life. Results: Thirteen studies were included. Exercise was divided into the following four modes: aerobic exercise, resistance exercise, a combination (aerobic and resistance exercises), and yoga or physical activity. Aerobic and resistance training had a mixed effect on pregnant women's quality of life, while the combination of aerobic and resistance exercises and yoga or physical activity resulted in significant improvements. Conclusions: This systematic review is the first to suggest that group-based combined exercise and yoga or physical activity are associated with significant benefits related to improvements in pregnant women's quality of life. Furthermore, aerobic or resistance exercise could potentially improve pregnant women's quality of life. Therefore, it is recommended that medical service providers should pay more attention to the importance of exercise, and develop tailored exercise programmes to promote improvements in pregnant women's quality of life.